MENINGKATKAN HASIL BELAJAR LARI SPRINT MELALUI PENERAPAN PENDEKATAN BERMAIN PADA SISWA KELAS XII SMK SWASTA JOSUA MEDAN T.A. 2017/2018 - Domarro L. Tamba (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2018)
The purpose of this study was to improve learning outcomes for sprinting through the application of a play approach to class XII students of Josua Private Vocational School Medan T.A. 2017/2018. The research method used in this research is Classroom Action Research. The location of this research is at the Josua Private Vocational School in Medan. The recipients of the action in this study were all students of class XII AP SMK Swasta Josua Medan T.A. 2017/2018 totaling 37 students. According to the results, it can be said that through the application of the play approach applied by the teacher, it ended in cycle II with the results of learning to run sprints in athletic learning which had been low to increase. The conclusion is "There is an increase in Sprint Running Learning Outcomes through the Application of the Playing Approach to Class XII Students of Josua Private Vocational School Medan T.A. 2017/2018.